Analisis Manajemen Risiko dengan Menggunakan SWOT dan Matriks 3x3 (Studi Kasus pada UMKM TEKO “Teh X Kopi”) - Ambardi, Alda Audia; Zulqisthi, Idzni Fatasya; Alamsyah, Iqbal (Universitas Serambi Mekkah, 2024)
Millennials and Generation Z are driving innovation in the tea and coffee market. The phenomenon has become a lifestyle that then creates many businesses in the food and beverage industry (FB) in Indonesia, and coffee and iced tea shops are one of the most prominent sectors. So that it creates competition between business behaviors. Therefore, risk management for businesses needs to be done to protect and minimize risks that can hinder the achievement of goals and various things that have the potential to cause losses. This research analysis is focused on UMKM TEKO (Teh X Kopi) with the aim of identifying sources of risk, analyzing risks, and treating risks. The method used in this research is SWOT Analysis, namely strengths, weaknesses, opportunities, and threats